Studi Penggunaan Obat Anti Tuberkulosis (OAT) Tahap Lanjutan pada Pasien Baru BTA Positif - Tista Ayu Fortuna; Hidajah Rachmawati; Didik Hasmono; Hidayah Karuniawati (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis will cause pain and death if not treated properly. OAT (Antituberculosis Drugs) is a treatment for tuberculosis patients. OAT has different dosage regimens and types of drugs. Treatment of TB patients consists of two phases (intensive and continuation phases). The continuation phase was at to kill dormant bacteria to prevent recurrence in patients. The purpose of this study was to determine and evaluate the pattern of using OAT in patients newly diagnosed rwith smear-positive at the continuation phase. This study is an observational descriptive study with results showing that the pattern of using OAT-KDT in patients was 89% and OAT-Separated was 11%. The pattern of using the OAT-KDT dose was 1x3 2KDT tablets. Another combination of antibiotics given to the patient is cotrimoxazole at a dose of 1x960mg. The side effect of OAT is an increase in serum transaminase and nausea each with a percentage of 23%. Based on the research, it can be concluded that the pattern of using OAT in Tuberculosis patients has followed the guidelines for the management of Tuberculosis treatment.